"Dyrektorium Duszpasterstwa Rodzin" przejawem troski Kościoła o małżeństwo i rodzinę - Gręźlikowski, Janusz (Ius Matrimoniale, 2006)
The sign of Church’s care in Poland about marriage and family is recently publication of Instruction priesthood of family through The Conference Episcopate of Poland. Its desire, in the presence visible and growing crisis marriage and family, to offer systematical help and support in priesthood of family. Collect, systematize and order principle and practice use in priesthood of family and propose new solution service conferment of marriage and family life new shape and size. Worth these essence, instructions and promises thoroughness to know, to study and to include in priesthood life the Church in Poland, and carry fruits in service family and marriage. Belong to hope that essences contents in Instruction miss to hearts and hands every priest and lay engagement in priesthood of family.